Carbamazepine-induced delayed-onset agranulocytosis in a case of bipolar disorder with Kikuchi's disease. Issue 6 (30th June 2021) - Irudayaraj, Cebasta; Innamuri, Raviteja; Kattula, Dheeraj
Abstract : A 48-year-old man who is a known case of bipolar disorder was maintaining well on a combination of carbamazepine and quetiapine for 3 years until he developed fever, severe leucopenia and lymphadenopathy, along with significant loss of weight and appetite. A thorough investigation revealed Kikuchi's disease as a likely histological diagnosis. Carbamazepine was discontinued and quetiapine was titrated for the management of psychiatric symptoms. The patient gradually made good recovery following discontinuation of carbamazepine and the diagnosis of drug-induced myelosuppression was retained. Clinicians need to be aware of the adverse effects of medications being used for long-term prophylaxis and other possible conditions that may change the course of drug effects.